Changes in tear film osmolarity after 25G+ PPV - J. Němčanský (BMC Ophthalmology, 2020)
Abstract Background The aim of our study was to assess changes of tear film osmolarity after micro-incision 25G+ pars plana vitrectomy (PPV) in a prospective study. Methods The group consisted of 21 patients (17 women, 4 men) with an average age of 70,52 years [48; 85]. All patients underwent 25G + PPV surgery due to a disorder of the vitreomacular interface (macular hole or epimacular membrane). Only patients who did not use artificial tears before the surgery and who had not been diagnosed with dry eye syndrome at ours or another institution were included in the study. Except cataract surgery, all ocular surface diseases, intraocular diseases, trauma or surgery were exclusion criterias. Tear film osmolarity was measured in both eyes in every patient before surgery, 10 days after surgery and 30 days after surgery. A paired test was used for statistical evaluation. Results No statistically significant change in osmolarity was found in the operated eyes (p > 0.05). No statistically significant changes in time (p > 0.05) were found when both eyes were compared. There were no postoperative complications or failure to observe the study protocol. Conclusion Micro-incision 25G + PPV does not affect the osmolarity of the tear film.